Barriers and facilitators on hand hygiene and hydro-alcoholic solutions' use: representations of health professionals and prevention perspectives - Nicolas Calcagni; Anne-Gaëlle Venier; Raymond Nasso; Guillaume Broc; Eva Ardichen; Bruno Jarrige; Pierre Parneix; Bruno Quintard (Elsevier, 2021)
Summary: Background: Healthcare-associated infections pose a serious problem in terms of health and mortality. Their prevention is a necessity, and healthcare professionals are one of their main vectors. Thus, they must be at the centre of preventative strategies. As hydro-alcoholic solutions (alcohol-based hand rub) represent the most effective means of preventing these infections, it is necessary to identify the representations, barriers, and facilitators of their use. Method: Forty-six healthcare professionals from two areas in France, New Aquitaine and Guadeloupe, were questioned about their practices through semi-structured registered interviews and four focus groups. Each interview and focus group were transcribed then analysed through lexicometric and thematic content analyses. Results: The interviewed identified several barriers and facilitators related to the composition and characteristics of hydro-alcoholic solutions (unpleasantness, harmfulness, personal preferences for other hand hygiene products), personal factors (work habits, cognitive bias, lack of knowledge and communication) and organizational (professional constraints, product accessibility, financial resources). Conclusion: Strategies to prevent healthcare-associated infections should be constructed with consideration of psychosocial facilitators and barriers for healthcare professionals in using hydro-alcoholic solutions. These strategies should also ensure that they are well informed about the effectiveness of alcohol-based solutions, through prevention campaigns and scientific articles. This awareness should equally be conveyed with educational tools that involve healthcare professionals and use the social dynamics of their work environment.